Danser et être dansé - Maria Acselrad (Ateliers d'Anthropologie)
I dance, she dances, we dance: an agentive dimension characterises the act of dancing. In the dance of the caboclinhos (Pernambuco, Brazil), we are invited to reflect on who is dancing and who is danced during this performance. The caboclinhos are carnival gatherings made up of men, women and children dressed up as Amerindians armed with bows and arrows, parading through the outlying districts of towns in the Pernambuco region. Their dances, literally called “manoeuvres”, evoke war movements. Beyond the forces mobilised to determine who dances the most and dances best, another battle is at play in the spiritual domain. The caboclinhos are linked to Jurema, an Afro-indigenous religion that worships the caboclos (ancestral spirits of indigenous people, warriors and healers). In the aesthetic of north-eastern Brazil, the understanding of the “world as a battle” is central to conceiving of the ethos of this religion (Lagrou and Gonçalves, 2013). It is therefore necessary to shine a light on the agonistic dimension of this practice in order to comprehend this dance as a corporeal experience infused with forces of opposition.